Pulsed electric field assisted rehydration of dry-salted cod (Gadus morhua) - Jessica Genovese; Silvia Tappi; Urszula Tylewicz; Fabio D'Elia; Ana De Aguiar Saldanha Pinheiro; Pietro Rocculi (ISEBTT, 2022)
Salted cod (G. morhua) is a highly appreciated product, traditionally imported by Mediterranean countries and commercialised with different moisture content depending on the extension of the dehydration process. Dry-salted cod must be rehydrated before consumption and this step can take up to five days.Desalting of cod on an industrial scale is usually carried out immersing the product in stagnant water, resulting not only in sample rehydration but also in the loss of salt. It therefore poses many problems, mainly related to the long processing times and the quality of the final product. For this reason, many researchers have focused on finding new desalting methods to improve mass transfer. The application of pulsed electric field (PEF) has been proposed as an alternative method to improve mass transfer in many food processes. However, there is no previous literature on the use of PEF to improve animal tissue rehydration. Therefore, the aim of this work was to investigate the influence of two PEF pre-treatments (PEF (1) -500 V·cm-1 and PEF (2) -1000 V·cm-1) on mass transport kinetics during the rehydration process of salted cod. Samples were treated at room temperature in tap water, with an initial electrical conductivity of 396 ± 5 μS·cm-1 at 25 °C (EC-meter Mod. Basic 30, Crison, Spain). Trials were conducted filling the treatment chamber with a productto- water ratio of around 1:5 (w/w) and delivering n=1000 pulses at fixed amplitude (10 ± 1 μs) and frequency (100 Hz). The rehydration process was carried out under static conditions for 6 days, immersing dry-salted cod samples in tap water (5 ± 0.5 °C) using a ratio of cod:water of 1:10 (w/v). Mass transfer parameters were determined at 0, 4, 6, 24, 48, 72, 96,120 and 144 h of the rehydration process. The results show that the use of PEF technology increases the rate of the rehydration process of dry-salted cod and influences the redistribution of salt. In general, the samples pre-treated with PEF showed higher weight gain and lower salt loss than the control ...